Yellow Corn Bird's nests, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
The postcard shows the nests of the Yellow Corn Bird or Yellow Oriole in a tree.
Colour: Sepia (print); Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Animals--Habitations--Trinidad and Tobago; Nests--Trinidad and Tobago; Birds--Trinidad and Tobago; Yellow Corn Bird